Strategic Implementation of Assessment “for” and “as” Learning in Science Education - Muhammad Minan Chusni (Universitas Lambung Mangkurat, 2022)
The relatively needed assessments at this time are assessment for learning and assessment as learning. This study discusses the strategy to adopt these assessments in science class. The method used is a literature study by reviewing relevant research results from books and relevant article results. The criteria for the articles discussed are related to assessment of learning, assessment for learning, and assessment as learning. The research findings provide three strategies to conduct an assessment for learning and assessment as learning that are 1) self-assessment, 2) peer-assessment, and 3) feedback. We hope that these results can provide a new perspective for teachers in making assessment schemes.